The Role of Program Evaluation in the Decision-Making Process - Raluca ANTONIE (Transylvanian Review of Administrative Sciences, 2011)
The decision of not organizing a Program Evaluation System at country level government has many negative implications as far as the decision-making process is concerned. The lack of political responsiveness, fiscal discipline and institutional effectiveness are part of the effects. The government does not require a coherent, solid evaluation system and, in exchange, it gets ‘Bleak House’- type reports. Program evaluation offers the adequate tools to do evidence-based decision-making on public policy priorities and public resource allocation.